Knowledge, attitude, and practice on blood donation among undergraduate first-year engineering students in Nepal - Bhola Teli; Durga Rijal; Sulochan GC; Ashok Khanal; Anil Kumar Singh (PLoS ONE, 2026)
Background Blood donation is essential for healthcare, yet maintaining a safe supply remains a challenge in low- and middle-income countries like Nepal. While university students are a key donor demographic, data on engineering students—a group with distinct academic profiles—is limited. This study assessed the knowledge, attitudes, and practices (KAP) regarding blood donation and identified the associated factors of these domains among first-year engineering students in Nepal. Methods A cross-sectional study was conducted between April and June 2022 among 191 students at the Pulchowk Engineering Campus, Tribhuvan University. Data were collected via a structured online questionnaire. Associated factors of knowledge and attitude (continuous scores) were identified using multivariable linear regression, while associated factors of donation practice were analyzed using multivariable logistic regression. Internal consistency was assessed using Cronbach’s alpha. Results The mean knowledge score was 13.91 (±3.81) out of 23, and the median attitude score was 7.00 (IQR: 1.00). Although attitudes were highly favorable, actual donation practice was low (16.8%). Multivariable linear regression showed that male students had significantly lower knowledge scores than females (B = −1.26, p = 0.048), and knowledge was the sole significant associated factor with positive attitudes (B = 0.04, p = 0.025). Logistic regression revealed that age ≥ 20 years (OR = 2.83, p = 0.030) and being male (OR = 4.20, p = 0.029) were strongly associated factors of donation practice, while civil engineering students were less likely to donate than those in other programs (OR = 0.38, p = 0.024). The primary barriers reported were “no specific reason” and “lack of opportunity.” Conclusion A descriptive “knowledge-practice gap” exists among engineering students. While females are more knowledgeable, males are more likely to donate. Interventions should move beyond general awareness toward structural mobilization, such as regular on-campus donation drives, to convert high ideological support into active practice.